Silver-modified Ba0.5Sr0.5Co0.8Fe 0.2O3-d as cathodes for a proton conducting solid-oxide fuel cell - Lin, Y.; Ran, R.; Shao, Zongping (2010)
Electrochemical performance of silver-modified Ba0.5Sr 0.5Co0.8Fe0.2O3-d (BSCF-Ag) as oxygen reduction electrodes for a protonic intermediate-temperature solid-oxide fuel cell (SOFC-H+) with BaZr0.1Ce0.8Y 0.1O3 (BZCY) electrolyte was investigated. The BSCF-Ag electrodes were prepared by impregnating the porous BSCF electrode with AgNO3 solution followed by reducing with hydrazine and then firing at 850 °C for 1 h. The 3 wt.% silver-modified BSCF (BSCF-3Ag) electrode showed an area specific resistance of 0.25 O cm2 at 650 °C in dry air, compared to around 0.55 O cm2 for a pure BSCF electrode. The activation energy was also reduced from 119 kJ mol-1 for BSCF to only 84 kJ mol-1 for BSCF-3Ag. Anode-supported SOFC-H+ with a BZCY electrolyte and a BSCF-3Ag cathode was fabricated. Peak power density up to 595 mW cm-2 was achieved at 750 °C for a cell with 35 µm thick electrolyte operating on hydrogen fuel, higher than around 485 mW cm-2 for a similar cell with BSCF cathode. However, at reduced temperatures, water had a negative effect on the oxygen reduction over BSCF-Ag electrode, as a result, a worse cell performance was observed for the cell with BSCF-3Ag electrode than that with pure BSCF electrode at 600 °C. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.